Dental caries and childhood obesity: roles of diet and socioeconomic status - Marshall TA, Eichenberger-Gilmore JM, Broffitt BA, Warren JJ, Levy SM. (Blackwell Synergy, 2007)
Our objective was to determine (a) if caries and obesity were associated in a pediatric population and (b) if so, then to explore diet and socioeconomic status as additional risk factors